Minorities and the state changing social and political landscape of Bengal - Dasgupta, Abhijit; Togawa, Masahiko; Barkat, Abul.; Sage eBooks (New Delhi ; London : SAGE, 2011)
This text discusses the enormity of problems faced by two numerically significant religious minority groups - Hindus in Bangladesh and Muslims in West Bengal, India.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Group identity -- India -- Bengal; Minorities -- Civil rights -- India -- Bengal; Migration, Internal -- India -- Bengal; Bengal (India) -- Politics and government; Electronic books